Disparities in Social Development: An Inter-Block Level Study of Bankura District, West Bengal - Tanmoy Dhibor (Modern Advances in Geography, Environment and Earth Sciences Vol. 6, 2021)
The degree of economic and social development all over the globe has both spatial and temporal disparities while development depends on the presence of some explicit determinants. Development disparity is studied in various scales, from global to local level. The primary goals of the present study are to assess the level of inter-Block disparity in social development in Bankura District of West Bengal and to unearth the forces and factors instrumental to such disparity. A total of 10 social indicators have been taken into consideration for the present analysis, while the Block level variation of development has been computed with the use of Development Index (DI). The results clearly exhibit wide variation among the Blocks in terms of social development. Nearly 10 Blocks, located on the plain areas of eastern part of the District experience social development to a satisfactory level, whereas 7 Blocks along the western plateau margin shows poor level of development. Lack of literacy, unawareness, inconvenient communication, and unsustainable public schemes are some of the identified factors which have played critical role behind the spatial disparity in social development. To reduce the disparity among the Blocks and equitable distribution of opportunities among the social groups in the hierarchical system, adaptation of suitable measures is sought at immediate basis.